Integration of Human Resources Capabilities and Organizational Innovation to Improve the Competitive Performance of MSMEs in Makassar City - Iwan Perwira; Hernita; Jumiati Syam3; Sitti Mujahida Baharuddin; Rohani Purnamasari Dima (LPPM STIEM BONGAYA, 2026)
This study aims to analyse the impact of human resource capabilities and organisational innovation on the competitive performance of micro, small, and medium enterprises (MSMEs) in Makassar. MSMEs play a vital role in the national economy but face numerous challenges in enhancing their competitiveness amid technological changes and market dynamics. Therefore, strengthening the internal capacity of organisations is crucial for improving business performance. Employing a quantitative approach with an explanatory design, this research elucidates the relationship between human resource capabilities, organisational innovation, and competitive performance in MSMEs. Data were collected via a survey of 150 MSME operators selected through purposive sampling, ensuring that participants had been in operation for at least two years. The research instrument utilised a five-point Likert scale questionnaire. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via the SmartPLS software. Findings indicate that human resource capabilities positively influence both organisational innovation and competitive performance, while organisational innovation also contributes positively to enhancing competitive performance. These results underscore the importance of developing competencies and innovative capabilities as key factors in strengthening the competitiveness and sustainability of MSMEs. Keywords: HR Capabilities, Organisational Innovation, Competitive Performance, SMEs, Competitiveness.